2022
DOI: 10.3390/brainsci12030343
|View full text |Cite
|
Sign up to set email alerts
|

Switching and Combining Device-Aided Therapies in Advanced Parkinson’s Disease: A Double Centre Retrospective Study

Abstract: Background: Device-aided therapies (DAT), such as continuous subcutaneous apomorphine infusion (CSAI), levodopa-carbidopa intestinal gel infusion (LCIG), and deep brain stimulation of the subthalamic nucleus (STN-DBS), have markedly changed the treatment landscape of advanced Parkinson’s disease (aPD). In some patients, it is necessary to switch or combine DATs for various reasons. The aim of this retrospective study was to explore the frequency and reasons for switching between or combining DATs in two moveme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…LCIG treatment was discontinued in case of severe adverse effects, in case of switch to another device‐aided treatment, 20 lack of caregiver, unrelated severe diseases that interfered with treatment also in case of reduced effectiveness of LCIG in very advanced disease stage. The decision to discontinue treatment was made by a multidisciplinary team and in agreement with patient and/or caregiver after a detailed in hospital evaluation of the patient and taking into consideration the efficiency of LCIG on multiple aspects of advanced PD with an emphasis on patient's and caregiver's quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…LCIG treatment was discontinued in case of severe adverse effects, in case of switch to another device‐aided treatment, 20 lack of caregiver, unrelated severe diseases that interfered with treatment also in case of reduced effectiveness of LCIG in very advanced disease stage. The decision to discontinue treatment was made by a multidisciplinary team and in agreement with patient and/or caregiver after a detailed in hospital evaluation of the patient and taking into consideration the efficiency of LCIG on multiple aspects of advanced PD with an emphasis on patient's and caregiver's quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…This is also supported by several recent studies, which have shown that patients also benefit from a combination or sequential application of various intensified therapies. Several retrospective case series show that both the combination and the sequential use of intensified therapeutic procedures can lead to significant clinical improvement (Sesar et al 2019;Georgiev et al 2022;Pürner et al 2023). This is supported by a small prospective case series that showed a significant decrease in motor impairment with the addition of LCIG in patients with DBS and therapy-refractory symptoms (Regidor et al 2017).…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 90%
“…33 Only few analyses consider patients with more than 1 AT change. 22,[31][32][33] No randomized blinded trials are available. The vast majority of studies to date attribute the decision to combine ATs to insufficient motor control [21][22][23][24][25][26][29][30][31][32][33][34][35] and adverse effects of the previous AT 21,25,26,[31][32][33][34][35] and document a relevant clinical improvement by combining ATs, in regard to main symptoms of PD 20,24,30,32 or motor complications.…”
Section: Discussionmentioning
confidence: 99%
“…22,[31][32][33] No randomized blinded trials are available. The vast majority of studies to date attribute the decision to combine ATs to insufficient motor control [21][22][23][24][25][26][29][30][31][32][33][34][35] and adverse effects of the previous AT 21,25,26,[31][32][33][34][35] and document a relevant clinical improvement by combining ATs, in regard to main symptoms of PD 20,24,30,32 or motor complications. [20][21][22][23]25,26,29,30,35 In 2 studies, CSAI was used as bridging therapy to DBS, 20,33 2 special cases used DBS for controlling biphasic-like dyskinesias induced by LCIG therapy, 27,28 and 1 study used LCIG as a rescue for DBSunresponsive new freezing of gait after STN-DBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation